2005
DOI: 10.1111/j.1440-1797.2005.00418.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between sleep complaints and proinflammatory cytokines in haemodialysis patients

Abstract: Proinflammatory cytokines, IL-1beta in particular, might be associated with sleep complaints in HD patients. OSAS is not uncommon in HD patients with sleep-related complaints and sleep architecture does not appear to be effected by the HD procedure itself.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 39 publications
0
21
0
2
Order By: Relevance
“…In addition to melatonin, it has also been suggested that altered cytokine levels have a role in sleep disorders (17). Chronic inflammation, as determined by altered cytokine levels, is highly prevalent in patients with end-stage renal disease (16).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to melatonin, it has also been suggested that altered cytokine levels have a role in sleep disorders (17). Chronic inflammation, as determined by altered cytokine levels, is highly prevalent in patients with end-stage renal disease (16).…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately much of these data are hard to interpret due to the bidirectional relationship with sleep, and the propensity for the use of cross-sectional studies in this research. For example, the relationship has been extensively studied in dialysis patients, but the study designs make it difficult to tell if sleep disturbances are a consequence or a cause of inflammation (Bilgic et al, 2007;Chiu et al, 2009;Erten et al, 2005;Gul et al, 2006;Lee et al, 2009;Li et al, 2012;Pertosa et al, 2000;Razeghi et al, 2012;Shiohira et al, 2011;Taraz et al, 2013;Yang et al, 2007). In inflammatory bowel disease (IBD), sleep disturbances, including prolonged sleep latency, frequent sleep fragmentation and inefficient sleep are common.…”
Section: Insomnia or Sleep Disturbances And Inflammationmentioning
confidence: 99%
“…(4) Psychologic factors: The SF-36 MCS score was used to assess the role of psychologic well-being in sleep quality. (5) Comorbid disease: Patients who undergo dialysis often have substantial comorbidity and exhibit elevated levels of inflammatory markers (38,39), both of which have been associated with reduced sleep quality (40). Therefore, our models examined diabetes; the cause of kidney failure; comorbidity as measured by ICED (21); and fibrinogen, IL-6, and C-reactive protein levels.…”
Section: Selection Of Covariatesmentioning
confidence: 99%